Computational Fluid Dynamics and Heat Transfer Analysis for a Novel Heat Exchanger - Ma, Haolin; Oztekin, Dennis E.; Bayraktar, Seyfettin; Yayla, Sedat; Oztekin, Alparslan (ASME, 2015)
Computational fluid dynamics (CFD) and heat transfer simulations are conducted for a novel heat exchanger. The heat exchanger consists of semi-circle cross-sectioned tubes that create narrow slots oriented in the streamwise direction. Numerical simulations are conducted for Reynolds numbers (Re) ranging from 700 to 30,000. Three-dimensional turbulent flows and heat transfer characteristics in the tube bank region are modeled by the k-e Reynolds-averaged Navier-Stokes (RANS) method. The flow structure predicted by the two-dimensional and three-dimensional simulations is compared against that observed by the particle image velocimetry (PIV) for Re of 1500 and 4000. The adequate agreement between the predicted and observed flow characteristics validates the numerical method and the turbulent model employed here. The three-dimensional and the twodimensional steady flow simulations are compared to determine the effects of the wall on the flow structure. The wall influences the spatial structure of the vortices formed in the wake of the tubes and near the exit of the slots. The heat transfer coefficient of the slotted tubes improved by more than 40% compare to the traditional nonslotted tubes.
Keywords: heat transfer; slotted tube; computational fluid dynamics; turbulence; Reynolds-averaged Navier-Stokes; CROSS-FLOW; REYNOLDS-NUMBER; OPTIMAL-DESIGN; TUBE BANKS; FIN; OPTIMIZATION; PAIR; Thermodynamics; Engineering